A brief appraisal of computational modeling of antimicrobial peptides' activity. Issue 1 (21st October 2018) - Mondal, Jagannath
Abstract: We present a brief overview of computer simulations over the span of last two decades that have made some serious attempts in providing key insights toward the mechanistic aspects of antimicrobial peptides and biomimetic peptides. We review some of the success stories of computational modeling of antimicrobial activity and also point toward the present shortcomings of the current approaches. Finally, we shed light upon the future potential directions that computational approach can adopt toward direct and closer comparisons with experiments on antimicrobial activity.